2022
DOI: 10.1002/app.52657
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of polypropylene nanofibrous membrane for the filtration of textile wastewater

Abstract: A fibrous membrane being prepared from nanofiber is of great demand for super‐efficient filtration of industrial wastewater. This study reported a highly efficient noanofibrous membrane made of superfine polypropylene (PP) nanofiber with an average diameter of only 228 nm and that had also demonstrated a direct influence of fiber diameter on its properties and performance for textile wastewater purification. The PP nanofibers were prepared with a varying content of PP/ethylene‐co‐vinyl alcohol (EVOH) blends fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“… SEM images of melt-electrospun polyolefin nanofibers from some recent investigations, a PP [ 113 ] permission with John Wiley & Sons, Inc., b PP [ 114 ] permission with John Wiley & Sons, Inc., c PE [ 110 ] permission with John Wiley & Sons, Inc., d PE [ 109 ], e PP/PVB blend [ 113 ] permission with John Wiley & Sons, Inc., and f PE/PVB blend [ 113 ], g PP from CAB/iPP [ 115 ], h PP [ 104 ], i PP from PP/EVOH film [ 104 ], j PP from PP/EVOH/PP film [ 104 ], k SAN/iPP [ 116 ] blend; l PP electrospun in vacuum [ 100 ] …”
Section: Electrospinning Of Polyolefinsmentioning
confidence: 99%
See 3 more Smart Citations
“… SEM images of melt-electrospun polyolefin nanofibers from some recent investigations, a PP [ 113 ] permission with John Wiley & Sons, Inc., b PP [ 114 ] permission with John Wiley & Sons, Inc., c PE [ 110 ] permission with John Wiley & Sons, Inc., d PE [ 109 ], e PP/PVB blend [ 113 ] permission with John Wiley & Sons, Inc., and f PE/PVB blend [ 113 ], g PP from CAB/iPP [ 115 ], h PP [ 104 ], i PP from PP/EVOH film [ 104 ], j PP from PP/EVOH/PP film [ 104 ], k SAN/iPP [ 116 ] blend; l PP electrospun in vacuum [ 100 ] …”
Section: Electrospinning Of Polyolefinsmentioning
confidence: 99%
“…In addition, Zhu et al [ 78 ] observed the outstanding separation performance of TiO 2 and dyeing wastewater with the excellent pure water flux of PP micro/nanofibrous membrane over the microporous membrane. Recently, Zakaria et al [ 114 ] developed a membrane from superfine PP nanofibers that is highly desired for efficient filtration of industrial wastewater. In that study, a PP nanofibrous membrane with an average fiber diameter of 228 nm was used, and it was shown that the fiber diameter has a direct effect on its properties and how well it cleans textile wastewater.…”
Section: Applications Of Polyolefin Nanofibermentioning
confidence: 99%
See 2 more Smart Citations